LANGUAGE ACQUISITION AND LANGUAGE LEARNING ACCORDING TO THE BEHAVIORISM AND NATIVISM THEORY WHILE AL-QUR’AN PERSPECTIVE - Sarwadi, Sarwadi (Bajang Institute, 2024)
Language acquisition and language learning is the nature of every human being, whether it’s done consciously or unconsciously because every human being communicates used oral and writing communication as directly and indirectly. Based on the covarative linguistic, various theories about language acquisition and laguage learning have emerged. This research method uses descriptive qualitative with a comparative approach. Meanwhile, the data in this research are the theories of nativism and behaviorism seen from the perspective of the Al-Qur'an. Based on the comparative analysis of the two theories seen from the perspective of the Al-Qur'an, it can be concluded that language acquisition and Language learning is carried out before the child is born, this can be seen from what have saide by the Allah